The Jangha (wall) of the Shiva Temple (Temple 3) - Temples of India Project Team (Jio Institute, 2024)
The jangha (wall) of the Shiva Temple (Temple 3) features plain pilasters projecting out of the surface, while the top portion is adorned with an ardhapadma (half-lotus motif) enclosed by a garland loop. Above the jangha, a varandika (moulded parapet) is placed, which features the antarapatta (recesses between mouldings) between two kapotapalikas (cyma recta moulding). Above the varandikas, miniature shikharas (spires) are placed which creates the anekandaka shikhara (multispired superstructure).